Drained mucosal advancement flap versus rerouting Seton around the internal anal sphincter in treatment of high trans-sphincteric anal fistula: A randomized trial. (December 2019) - Abdelnaby, Mahmoud; Emile, Sameh; El-Said, Mohamed; Abdallah, Emad; AbdelMawla, Ahmed
Abstract: Background: Several sphincter saving techniques have been described for complex anal fistula (CAF) with variable outcomes. The present trial aimed to compare two techniques for CAF; the drained mucosal flap technique and rerouting Seton around the internal anal sphincter (IAS). Methods: Adult patients with high trans-sphincteric anal fistula were randomly assigned to one of two groups: group I underwent mucosal advancement flap with drainage Seton rerouted around the external anal sphincter, and group II underwent rerouting Seton around the IAS. The two groups were compared in terms of the incidence of postoperative fecal incontinence (FI), healing of fistula, complications, and changes in anal pressures. Results: 97 patients (80 male) of a mean age of 39.5 years were included. One patient developed FI in group I versus 7 in group II (p = 0.03). Failure of healing occurred in 2 patients in group I and 4 in group II (p = 0.43). In group II, the average time for spontaneous fall of Seton was 14 ± 2.8 days whereas in group I the average time for removal of Seton was 40 ± 14.9 days (p < 0.0001). There were no significant differences between the two groups in complication rate. Postoperatively, the decrease in resting anal pressure was significant in Group II but not group I. Conclusion: The drained mucosal flap technique was associated with significantly lower incidence of FI, yet longer operative time and longer time to complete healing compared to rerouting Seton around the IAS. The success rates of both techniques was comparable. Highlights: 97 patients of a mean age of 39.5 years were included. Group I underwent drained mucosal flap. Group II underwent rerouting seton around IAS. One patient developed incontinence in group I versus 7 in group II. Failure of healing occured in 2 patients in group I and 4 in group II.